فعالية الإرشاد بالتأمل الفائق في خفض ضغط الصدمة الثانوي لدى أمهات الأطفال ذوي الإعاقة العقلية البسيطة - السيد، خلف أحمد مبارك Alsayed, Khalaf Ahmed Mubarak; عبدالحافظ، ليلى عبدالحميد; أحمد، أمل عبدالفتاح فؤاد (جامعة الوادي الجديد - كلية التربية, 2023)
هدف البحث الحالي التعرف على فعالية برنامج إرشادي قائم على التأمل الفائق في خفض ضغط الصدمة الثانوي لدي أمهات أطفال ذوي الإعاقة العقلية البسيطة. وتكونت عينة البحث من عينة إرشادية عددها (8) من أمهات الأطفال ذوي الإعاقة العقلية البسيطة المسجلين بمركز حسن حلمي لتأهيل الإعاقة في محافظة الوادي الجديد – مدينة الخارجة. تتراوح أعمارهن ما بين (30 – 50) سنة، واستخدم البحث مقياس ضغط الصدمة الثانوي إعدادا (Bride et al 2004- ترجمة وتعريب الباحثة)، والبرنامج الإرشادي للأمهات إعداد الباحثة وأسفرت نتائج البحث عن وجود فرق بين متوسطي رتب درجات القياسين القبلي والبعيد في خفض ضغط الصدمة الثانوي لصالح القياس العبدي، وعدم وجود فرق بين القياسين العبدي والتابعي للمجموعة الإرشادية مما يدل على استمرارية أثر البرنامج في خفض ضغط الصدمة الثانوي. The current research aimed to identify the effectiveness of a counseling program based on ultra-meditation in reducing secondary traumatic stress among mothers of children with mild mental disabilities. The research sample consisted of one experimental sample of (8) mothers of children with mild mental disabilities who were registered at the Hassan Helmy Center for Rehabilitation of Disabilities in the New Valley Governorate - Kharga City. Their ages ranged between (30-50) years, and the research used the tools of the secondary shock pressure scale prepared by (Bride, Robinson, Yegidis, & Figley, 2004 - translation of the researcher's Arabicization), and the counseling program for mothers prepared by the researcher. The results of the research revealed that there is a difference between the pre and post applications. In reducing secondary traumatic stress in favor of post-measurement, and the absence of a difference between the post- and follow-up measurements of the extension group, which indicates the continuity of the impact of the program in reducing secondary traumatic stress. their traumatic stress.
Keywords: الإعاقة العقلية -- البرامج الإرشادية -- صعوبات التعلم -- الاضطرابات النفسية